Strategically Integrating AI, Digital Twins, and Hybrid Work Design in Human Resource Administration - Isa Kholili; Hamdan Arif Fatoni (Idarotuna : Journal of Administrative Science, 2026)
The literature on AI-driven Human Resource Administration remains fragmented across strategic HRM, information systems, and ethics, lacking an integrative framework. This study synthesizes 122 sources through systematic, multidisciplinary thematic synthesis, consolidating findings across four interconnected dimensions: AI-driven reconfiguration of recruitment, training, and performance management; strategic realignment of HRA toward agility and sustainability; hybrid job design as a boundary condition involving autonomy and well-being; and ethical governance challenges surrounding algorithmic bias, explainability, and data privacy. The synthesis reveals that strategic value depends on three synergistic mechanisms—human-AI collaboration preserving contextual judgment, adaptive hybrid job design fostering productivity and mental health, and human-centered governance ensuring fairness. Critical gaps emerge, including scarce longitudinal evidence on digital twin effectiveness, under-theorized cross-cultural AI ethics, and weak sustainability metric integration. We propose an “Ethically-Augmented Strategic HRA” model bridging these domains and outline a targeted research agenda. The paper contributes by integrating strategic HRM, technology management, and ethics literatures, offering actionable pathways for practitioners and policymakers.